2018
DOI: 10.1088/1361-6528/aaa6bd
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of ZnO-based flexible nano generators via a sol–gel technique for sensing and energy harvesting applications

Abstract: Zinc oxide (ZnO) is a remarkable inorganic semiconductor with exceptional piezoelectric properties compared to other semiconductors. However, in comparison to lead-based hazardous piezoelectric materials, its features have undesired limitations. Here we report the 5~6 folds enhancement in the piezoelectric properties via chemical doping of copper matched to intrinsic ZnO. The flexible piezoelectric nanogenerator (F-PENG) device was fabricated using an unpretentious solution process of spin coating with other a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 47 publications
1
18
0
Order By: Relevance
“…The peak at 276 cm -1 is related to the B 2 s order mode with low intensity. The broad feature between 1100 and 1200 cm -1 is assigned to the two phonon modes (2LO), characteristic of II-IV semiconductors [8,50].…”
Section: Raman Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…The peak at 276 cm -1 is related to the B 2 s order mode with low intensity. The broad feature between 1100 and 1200 cm -1 is assigned to the two phonon modes (2LO), characteristic of II-IV semiconductors [8,50].…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…Zinc oxide (ZnO) is known as an important semiconductor for its favorable properties as transparency [1], high electron mobility [2], wide band gap [3], tough room temperature [4] and luminescence [5]. In the last few years, there has been a growing interest of the researchers, focusing on the synthesis of nanocrystalline ZnO, hence, many methods, including sol-gel [6][7][8][9]. Thereby, particle size and crystal morphology play important roles in all applications, like nanodevices for opto-electronic [10], gas sensing [11], photocatalytic activity [12].…”
Section: Introductionmentioning
confidence: 99%
“…ZnO is one of the most promising semiconducting materials, which has received significant attention owing to its unique and easily tunable physical and chemical properties [111]. It is known that the ZnO is an intrinsic n-type semiconductor.…”
Section: Introductionmentioning
confidence: 99%
“…Maamet et al [ 9 ] presented the main characteristics of piezoelectric material types, as shown in Table 1 [ 63 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ].…”
Section: Piezoelectric Materialsmentioning
confidence: 99%